Labor Induction versus Expectant Management: Evaluating Maternal and Neonatal Outcomes in Low-Risk Nulliparous Women - Divya Raghavendra Rao; G. D. Abilashini; Vijayalakshmi Gnanasekaran (Journal of Pharmacy and Bioallied Sciences, 2025)
Aim: This study aimed to compare the maternal and neonatal outcomes of elective labor induction at 39 weeks with expectant management in low-risk nulliparous women. Materials and Methods: A randomized controlled trial was conducted at ACS Medical College and Hospital, Chennai, over 6 months. A total of 100 low-risk nulliparous women with singleton pregnancies between 38 weeks 0 days and 38 weeks 6 days of gestation were randomized into two groups: labor induction (n = 50) and expectant management (n = 50). Statistical analysis was performed using an independent t-test to compare two groups, with a significance level of P < 0.05. Results: The labor induction group had a shorter labor duration (7.5 ± 2.3 vs. 9.2 ± 2.7 h; P = 0.003). The mode of delivery was similar, with vaginal births at 72% versus 64% (P = 0.34) and cesarean rates at 28% versus 36% (P = 0.42). Maternal complications (postpartum hemorrhage, P = 0.21; infection, P = 0.69) and neonatal outcomes (Apgar scores, birth weight, NICU admissions) showed no significant differences. Conclusion: Labor induction at 39 weeks in low-risk nulliparous women shortens labor duration without increasing cesarean delivery rates, maternal complications, or adverse neonatal outcomes. These findings support the safety of elective labor induction in this population.